Expandable, storage stable polymer beads

Expandable polyolefin beads, composed of PE, PP, or their mixtures with thermoplastic microspheres, address the challenges of transportation and density limitations by allowing stable storage and flexible foaming for tailored product properties, reducing costs and enhancing application flexibility.

JP7616997B2Active Publication Date: 2025-01-17SABIC GLOBAL TECHNOLOGIES BV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021532101
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-05
Filing Date
2019-11-20
Publication Date
2025-01-17
Estimated Expiration
2039-11-20

AI Technical Summary

Technical Problem

Current polyolefin beads are produced only in a foamed form, making transportation and storage complicated and expensive, and molders are limited in their ability to achieve desired densities for specific applications.

Method used

Developed expandable polyolefin beads composed of polyethylene (PE), polypropylene (PP), or mixtures thereof, encapsulating a blowing agent within thermoplastic microspheres, allowing storage and transportation in an unfoamed state and enabling foaming to desired densities for tailored product properties.

Benefits of technology

The expandable beads maintain storage stability and can be foamed to a wide range of densities, reducing shipping costs and providing molders with flexibility in density selection for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616997000010
    Figure 0007616997000010
  • Figure 0007616997000001
    Figure 0007616997000001
  • Figure 0007616997000002
    Figure 0007616997000002
Patent Text Reader

Abstract

The present invention relates to expandable beads comprising a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof, and b) thermoplastic microspheres encapsulating a blowing agent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to expandable polymer beads and their preparation. [Background technology]

[0002] Polymer bead-based foams offer the advantage of extremely low density and the production of large three-dimensional structures with complex shapes. They are widely used for various applications. Typical examples are packaging materials and parts for automotive applications, such as bumper cores, battery covers, arm rests, steering column pads, and floor spacers. Such bead foams are made of polymeric beads that contain a blowing agent or a combination of blowing agents.

[0003] A special class of beads are polyolefin-based beads, which result in a foamed structure with high dimensional stability, chemical resistance, and good mechanical properties. They can be produced, for example, by extrusion and autoclave processes. Both processes involve impregnating the beads with a gas under high pressure, resulting in foamed polyolefin beads, in which the gas acts as a blowing agent to expand the beads.

[0004] The extrusion process involves melting polyolefin resin pellets in an extruder, injecting a blowing agent into the polyolefin melt, and chopping the expanded polyolefin strands emerging from the extruder into foam beads.

[0005] The autoclave process involves two steps. First, polyolefin resin pellets are converted into polyolefin beads of the desired diameter by extrusion and underwater pelletizing processes. The second step of the process involves dispersing the polyolefin beads in water in an autoclave using a suspension aid, followed by heating the contents of the autoclave to a temperature above the softening point of the resin, and then injecting a blowing agent into the autoclave to impregnate the beads with the blowing agent. The high-pressure, hot-impregnated polyolefin beads are then discharged into a large flushing vessel maintained at atmospheric pressure. The resulting expanded polyolefin beads are separated from the water, dried, and packed for shipment.

[0006] The main disadvantage of currently produced polyolefin beads is that they are only produced in expanded form. The beads cannot be produced and stored in non-expanded form, because the gas acting as the blowing agent diffuses out of the beads, and they must be transported as expanded beads to a converter for shaping. This makes transportation and storage complicated and expensive. Another disadvantage is that the molder cannot produce and expand the beads to any desired density according to his requirements. This also limits the molder's options to use the beads at densities other than those supplied. Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, it is an object of the present invention to provide storage stable, expandable polyolefin beads. This means that the beads can be stored and / or transported in unexpanded form without loss or significant loss of blowing agent. This saves on transportation costs and gives molders the option to use products with a wide range of desired densities depending on their application. Another object is to provide a process for producing the beads. [Means for solving the problem]

[0008] The expandable beads according to the present invention are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Includes.

[0009] The polyolefin may thereby comprise the substrate and the thermoplastic microspheres may be dispersed within the substrate.

[0010] By applying the present invention, the above mentioned objectives are at least partially met. An advantage of the present invention is that the expandable beads of the present invention can be stored and / or transported in a non-expanded form without loss or significant loss of blowing agent. Furthermore, the expandable beads according to the present invention can be foamed over a wide range of desired densities depending on the product application. The desired density can be controlled by the conditions of the foaming process. This gives converters the freedom to tailor the properties of the final product to the application.

[0011] Preferably, the expandable beads comprise a polyolefin in the range of ≧70% to ≦98% by weight, preferably >75% to ≦98% by weight, more preferably ≧80% to ≦98% by weight, more preferably ≧85% to ≦98% by weight, the total amount of polyolefin and thermoplastic microspheres being 100% by weight.

[0012] In addition, the expandable beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The expandable beads preferably contain polyolefin in the range of ≧70% to ≦98% by weight, more preferably ≧85% to ≦98% by weight, with the total amount of polyolefin and thermoplastic microspheres being 100% by weight.

[0013] Beads comprising a binary mixture of polyolefins are Steam Chest This can be advantageous in the manufacture of articles by fusion, such as in molding processes. Such mixtures usually have two melting points, which ensures that the beads can be easily fused together while maintaining mechanical stability when molded at temperatures between the two melting points.

[0014] Polypropylene (PP) Preferably, the expandable beads comprise a mixture of polypropylene and polyethylene, with the amount of polypropylene by weight being greater than the amount of polyethylene.

[0015] Preferably, the amount of polypropylene in the expandable beads is greater than 60% by weight, preferably greater than 70% by weight, more preferably greater than 80% by weight, based on the total amount of polypropylene and polyethylene in the beads.

[0016] More preferably, the expandable beads comprise a polyolefin, the polyolefin being selected from polypropylene.

[0017] Preferably, the expandable beads comprise polypropylene in the range of ≧50% to ≦98% by weight, preferably >75% to ≦98% by weight, more preferably ≧80% to ≦98% by weight, more preferably ≧85% to ≦98% by weight, and the total amount of polyolefin and thermoplastic microspheres is 100% by weight.

[0018] Preferably, the melt flow index (MFI) of the polypropylene is in the range of >0.3 and <100 g / 10 min, preferably in the range of ≧2 to ≦60 g / 10 min, preferably in the range of ≧5.0 to ≦50 g / 10 min, more preferably in the range of ≧8 to ≦50 g / 10 min, when measured according to ISO 1133 at 230° C. and a load of 2.16 kg.

[0019] The foam beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The expandable beads comprise from ≧50% to ≦98% by weight, preferably from ≧80% to ≦98% by weight, of polypropylene, the total amount of polyolefin and thermoplastic microspheres being 100% by weight, and the polypropylene preferably has a melt flow index (MFI) in the range of >0.3 and <100 g / 10 min, measured according to ISO 1133 at 230° C. and a load of 2.16 kg.

[0020] The foam beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, It is further preferred that the expandable beads comprise in the range of ≧50% to ≦98% by weight, preferably ≧80% to ≦98% by weight, of polypropylene, the total amount of polyolefin and thermoplastic microspheres being 100% by weight, and the polypropylene has a melt flow index (MFI) in the range of ≧8 to ≦50 g / 10 min, as measured according to ISO 1133 at 230° C. and a load of 2.16 kg.

[0021] The polypropylene may be a random PP copolymer or a PP homopolymer or a PP-UMS or a mixture thereof. Preferably, the polypropylene is a random PP copolymer.

[0022] Preferably, the expandable beads are a) a polyolefin selected from polyethylene (PE), random polypropylene copolymers, and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The expandable beads comprise a random polypropylene copolymer in the range of ≧50% to ≦98% by weight, preferably ≧80% to ≦98% by weight, and the total amount of polyolefin and thermoplastic microspheres is 100% by weight; The melt flow index (MFI) of the random polypropylene copolymer is in the range of >0.3 and <100 g / 10 min when measured by ISO 1133 at 230° C. and 2.16 kg load.

[0023] More preferably, the expandable beads are a) a polyolefin selected from polyethylene (PE), random polypropylene copolymers, and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The expandable beads comprise a random polypropylene copolymer in the range of ≧50% to ≦98% by weight, preferably ≧80% to ≦98% by weight, wherein the total amount of polyolefin and thermoplastic microspheres is 100% by weight, and the melt flow index (MFI) of the random polypropylene copolymer is in the range of ≧8 to ≦50 g / 10 min, as measured by ISO 1133 at 230° C. and a load of 2.16 kg.

[0024] Random PP Copolymer Polypropylene compositions consisting of propylene copolymers are known. Propylene copolymers are obtained by copolymerizing propylene with one or more other olefins, preferably ethylene, under suitable polymerization conditions. The preparation of propylene copolymers is described, for example, in Moore, EP (1996) Polypropylene Handbook. Polymerization, Characterization, Properties, Processing, Applications, Hanser Publishers: New York.

[0025] Preferably, the PP copolymer is a copolymer of propylene and an α-olefin, for example an α-olefin selected from the group of α-olefins having 2 or 4 to 10 C atoms, for example the amount of α-olefin is less than 10 wt.%, based on the total propylene copolymer.

[0026] The copolymers of propylene and α-olefins can be made by any known polymerization technique and with any known polymerization catalyst system. With regard to the technique, reference can be made to slurry, solution or gas phase polymerization, and with regard to the catalyst system, reference can be made to Ziegler-Natta, metallocene or single-site catalyst systems. All are known in the art in their own right.

[0027] Homopolymer PP Polypropylene compositions comprising propylene homopolymers are known, which can be obtained by polymerizing propylene under suitable polymerization conditions.

[0028] The preparation of propylene homopolymers is described, for example, in Moore, EP (1996) Polypropylene Handbook. Polymerization, Characterization, Properties, Processing, Applications, Hanser Publishers: New York.

[0029] Homopolymer polypropylene can be made by any known polymerization technique and with any known polymerization catalyst system, with respect to the technique, reference can be made to slurry, solution or gas phase polymerization, and with respect to the catalyst system, reference can be made to Ziegler-Natta, metallocene or single site catalyst systems.

[0030] Low Density Polyethylene (LDPE) The manufacturing process for LDPE is summarized on pages 43-66 of the Handbook of Polyethylene by Andrew Peacock (2000; Dekker; ISBN 0824795466).

[0031] The term LDPE is understood herein to include both LDPE homopolymers and LDPE copolymers. LDPE copolymers are copolymers of ethylene with suitable comonomers well known to those skilled in the art, such as alkenes, cycloalkenes, and dienes. Suitable comonomers include α-olefins with 3-12 C atoms, ethylenically unsaturated carboxylic acids, ethylenically unsaturated C4-15 carboxylic acid esters or anhydrides thereof. Examples of α-olefins suitable for application as comonomers are propylene and / or butene. Examples of suitable ethylenically unsaturated carboxylic acids are maleic acid, fumaric acid, itaconic acid, acrylic acid, methacrylic acid, and / or crotonic acid. Examples of ethylenically unsaturated C4-15 carboxylic acid esters or their anhydrides are methyl (meth)acrylate, ethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, n-butyl methacrylate, vinyl acetate, methacrylic anhydride, maleic anhydride, 1,4-butanediol dimethacrylate, hexanediol dimethacrylate, 1,3-butylene glycol dimethacrylate, ethylene glycol dimethacrylate, dodecanediol dimethacrylate, trimethylolpropane trimethacrylate, trimethacrylate esters, and / or itaconic anhydride. Also, difunctional alkadienes, such as 1,5-hexadiene, 1,7-octadiene, 1,9-decadiene, and 1,13-tetradecadiene, may be applied. The amount of comonomer in the polymer depends on the desired application.

[0032] Preferably, the LDPE has a viscosity of 915 to 935 kg / m according to ISO 1183. 3and a melt flow rate of 0.10 g / 10 min to 80 g / 10 min measured at 190 °C and 2.16 kg according to ISO 1133:2011. Such LDPE can be obtained via high pressure radical polymerization of ethylene or of ethylene with one or more comonomers in an autoclave or tubular reactor.

[0033] Preferably, the LDPE has an Mn of at least 5.0 kg / mol by size exclusion chromatography, and an Mw of at least 50 kg / mol by size exclusion chromatography. The LDPE may have an Mn of at most 25.0 kg / mol, such as at most 20.0 kg / mol, for example at most 17.5 kg / mol, by size exclusion chromatography. The LDPE may have an Mw of at most 350 kg / mol, such as at most 330 kg / mol, for example at most 300 kg / mol, for example at most 250 kg / mol, by size exclusion chromatography. The LDPE may have an Mn of 5.0 to 10.0 kg / mol by size exclusion chromatography, and an Mw of 50 to 200 or 50 to 150 kg / mol by size exclusion chromatography. In other embodiments, the LDPE may have an Mn of 10.0 to 20.0 kg / mol by size exclusion chromatography, and an Mw of 150 to 250 or 150 to 200 kg / mol.

[0034] For size exclusion chromatography, polymer samples are dissolved (0.9 mg / ml) in 1,2,4-trichlorobenzene (TCB), which is distilled at 150°C for 4 hours before use and stabilized with butylhydroxytoluene (BHT) at a concentration of 1 mg / ml. The solution is filtered at high temperature (150°C) using a millipore filtration device (1.2 mm) placed in a Hereous LUT furnace operated at 150°C. Separation of polymers by molar mass may be performed on a Polymer Laboratories PL GPC210. ​​The SEC system is operated at high temperature (column bath at 160°C, injection bath at 160°C, and solvent reservoir at 35°C) with a flow rate of 0.5 ml / min. The eluent is 1,2,4-trichlorobenzene. To minimize shear degradation of high molar mass polymer chains, two Polymer Laboratories SEC columns with large particle size (PLGel mixed A-LS 20 mm columns) in series are used. A light scattering detector (WYATT DAWN EOS multi-angle laser light scattering detector) is placed in-line between the SEC and the refractive index detector. A dn / dc=0.097 ml / g is used.

[0035] Preferably, the LDPE is produced in a tubular reactor operated at a pressure of ≧200 and ≦280 MPa and at an average reaction peak temperature of ≧220°C and ≦300°C.

[0036] The LDPE may include one or more of the comonomers, which are fed to the tubular reactor at one or more feed ports of the reactor, and each comonomer is preferably fed to the tubular reactor in an amount of ≦2.0 mol % based on the total feed composition, such that the resulting ethylene copolymer has a comonomer content of at least ≧0.2 mol % and at most ≦6 mol % based on the total mol % of ethylene and the comonomer(s).

[0037] Linear low density polyethylene (LLDPE) The LLDPE according to the present invention is a copolymer of ethylene with at least one α-olefin.

[0038] Linear low density polyethylene (LLDPE) can be obtained, for example, by polymerizing ethylene with at least one α-olefin, which can be selected from 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, and / or 1-octene, preferably 1-butene.

[0039] Linear low density polyethylene (LLDPE) may be produced, for example, using at least one or exactly one metallocene catalyst or at least one or exactly one Ziegler-Natta catalyst.

[0040] Preferably, the linear low density polyethylene (LLDPE) used according to the present invention may be produced using at least one Ziegler-Natta catalyst comprising, for example, Mg and at least one or more of Ti, Hf, or Zr.

[0041] The copolymer of ethylene and at least one α-olefin has a viscosity of ≧850 kg / m3 and ≦950 kg / m3, preferably ≧910 kg / m3, as determined by, for example, ISO 1183-1:2012, method A. 3 And ≦940kg / m 3 , and more preferably 920 kg / m 3 from 930kg / m 3 The density may be between 0.01 and 0.1.

[0042] The LLDPE may, for example, have an MFI in the range of ≧0.1 g / 10 min to ≦100 g / 10 min, preferably ≧0.5 g / 10 min to ≦80 g / 10 min, more preferably ≧5 g / 10 min to ≦70 g / 10 min, still more preferably ≧6 g / 10 min to ≦60 g / 10 min, and more preferably ≧8 g / 10 min to ≦55 g / 10 min, when measured according to ISO 1131-1:2011 at 190° C. and a load of 2.16 kg.

[0043] LLDPE may preferably be manufactured using a gas phase or slurry process. The manufacturing processes for polyethylene are summarized in "Handbook of Polyethylene" by Andrew Peacock (2000; Dekker; ISBN 0824795466), pages 43-66.

[0044] Preferably, the expandable beads comprise polyethylene, the polyethylene being selected from linear low density polyethylene (LLDPE).

[0045] Preferably, the expandable beads comprise polyethylene, the polyethylene being selected from LLDPE having an MFI in the range of ≧5 to ≦70 g / 10 min, preferably ≧6.0 to ≦60 g / 10 min, more preferably ≧8 to ≦55 g / 10 min, measured according to ISO 1133 at 190° C. and 2.16 kg.

[0046] Preferably, the expandable beads comprise polyethylene, the polyethylene having a modulus of ≧910 to ≦940 kg / m as measured by ISO 1183. 3 in the range of ≧920 to ≦930 kg / m 3 The LLDPE is selected from LLDPEs having a density in the range of

[0047] Preferably, the expandable beads comprise polyethylene, the polyethylene having an MFI in the range of ≧5 to ≦70 g / 10 min, preferably ≧6.0 to ≦60 g / 10 min, more preferably ≧8 to ≦55 g / 10 min, as measured by ISO 1133 at 190° C. and 2.16 kg, and an MFI in the range of ≧910 to ≦940 kg / m, as measured by ISO 1183. 3 in the range of ≧920 to ≦930 kg / m 3 The LLDPE is selected from LLDPEs having a density in the range of

[0048] Most preferably, the expandable beads comprise polyethylene, the polyethylene having an MFI in the range of ≧5 to ≦70 g / 10 min, as measured by ISO 1133 at 190° C. and 2.16 kg, and an MFI of ≧910 to ≦940 kg / m, as measured by ISO 1183. 3 The LLDPE is selected from LLDPEs having a density in the range of

[0049] The foam beads are a) a polyolefin blend consisting of LLDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; may include:

[0050] The foam beads are a) a polyolefin blend consisting of LLDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; It may include, The amount of LLDPE is in the range of ≧0.5 to ≦25 wt. %, based on the total amount of polyolefin.

[0051] The foam beads are a) a polyolefin blend consisting of LLDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; It may include, The amount of LLDPE is in the range of ≧0.5 to ≦25 wt.% based on the total amount of polyolefin, the MFI of the LLDPE is in the range of ≧5 to ≦70 g / 10 min as measured at 190° C. and 2.16 kg according to ISO 1133, and the density of the LLDPE is in the range of ≧910 to ≦940 kg / m as measured according to ISO 1183. 3 is within the range.

[0052] Preferably, the expandable beads are a) a polyolefin blend consisting of LLDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; Including, The expandable beads comprise ≧60% to ≦98% by weight, more preferably ≧80% to ≦98% by weight, of polypropylene, based on the total amount of polyolefins, and ≧2% to ≦40% by weight, more preferably ≧2% to ≦25% by weight of LLDPE.

[0053] Preferably, the expandable beads are from ≧70% by weight to ≦98% by weight, Preferably >75% by weight to ≦98% by weight, More preferably ≧80% by weight to ≦98% by weight, More preferably, the polyolefin mixture is in the range of ≧85% by weight to ≦98% by weight of LLDPE and PP, The amount of polyolefin blend and thermoplastic microspheres is 100% by weight.

[0054] Preferably, the expandable beads are a) a polyolefin blend consisting of LLDPE and random PP; b) thermoplastic microspheres encapsulating a blowing agent; Includes.

[0055] High Density Polyethylene (HDPE) The expandable beads may comprise HDPE. The MFI of the HDPE may be in the range of ≧0.1 to ≦100 g / 10 min. Preferably, the MFI is in the range of ≧0.6 to ≦80 g / 10 min, more preferably ≧5 and ≦80 g / 10 min, more preferably ≧10 to ≦70 g / 10 min, more preferably ≧10 to ≦60 g / 10 min.

[0056] MFI is measured at 190°C and 2.16kg according to ISO1133-1:2011.

[0057] The density of high density polyethylene is ≥ 940 and ≤ 960 kg / m 3 , more preferably ≧945 to ≦955 kg / m 3 may be in the range.

[0058] Density is measured according to ISO 1183-1:2012.

[0059] The HDPE may be unimodal or multimodal HDPE, for example bimodal HDPE or trimodal HDPE. Preferably, the HDPE is bimodal HDPE.

[0060] The manufacturing process for HDPE is summarized in the "Handbook of Polyethylene" by Andrew Peacock (2000; Dekker; ISBN 0824795466) on pages 43-66. Suitable catalysts for the production of polyethylene include Ziegler-Natta catalysts, chromium-based catalysts, and single-site metallocene catalysts.

[0061] Unimodal polyethylene can be obtained, for example, by polymerizing ethylene and optionally at least one olefin comonomer in a slurry in the presence of a silica-supported chromium-containing catalyst and / or an alkyl boron compound. Suitable comonomers include, for example, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, and / or 1-octene.

[0062] Unimodal polyethylene can be obtained, for example, by polymerizing ethylene and optionally at least one olefin comonomer in a gas phase or slurry polymerization process.

[0063] The manufacturing process of bimodal high density polyethylene (HDPE) is summarized in "PE 100 Pipe systems" (ed. Bromstrup; 2nd edition, ISBN 3-8027-2728-2) on pages 16-20. The production of bimodal high density polyethylene (HDPE) via a low pressure slurry process is described in "Bimodal polyethylene-Interplay of catalyst and process" by Alt et al. (Macromol.Symp.2001, 163, 135-143). The properties of this polyethylene are determined, among other things, by the catalyst system and the concentrations of catalyst, comonomer, and hydrogen. The production of bimodal high density polyethylene (HDPE) via a low pressure slurry process can also be carried out via a three-stage process. The concept of a two-stage cascade process is explained in "Bimodal polyethylene-Interplay of catalyst and process" by Alt et al. (Macromol.Symp.2001, 163) on pages 137-138.

[0064] The foam beads are a) a polyolefin blend consisting of HDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; may include:

[0065] The foam beads are a) a polyolefin blend consisting of HDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; It may include, The amount of HDPE is in the range of ≧0.5 to ≦25 wt. %, based on the total amount of polyolefin.

[0066] The foam beads are a) a polyolefin blend consisting of HDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; It may include, The amount of HDPE is in the range of ≧0.5 to ≦25 wt.% based on the total amount of polyolefin, the MFI of the HDPE is in the range of ≧5 to ≦70 g / 10 min as measured at 190° C. and 2.16 kg according to ISO 1133, and the density of the HDPE is in the range of ≧940 to ≦960 kg / m as measured according to ISO 1183. 3 is within the range.

[0067] Preferably, the expandable beads are a) a polyolefin blend consisting of HDPE and PP; b) thermoplastic microspheres encapsulating a blowing agent; Including, The expandable beads comprise ≧60% to ≦98% by weight, more preferably ≧80% to ≦98% by weight, of polypropylene, based on the total amount of polyolefins, and ≧2% to ≦40% by weight, more preferably ≧2% to ≦25% by weight of HDPE.

[0068] Expandable beads are ≧70% by weight to ≦98% by weight, Preferably >75% by weight to ≦98% by weight, More preferably ≧80% by weight to ≦98% by weight, More preferably, the polyolefin mixture may comprise a polyolefin mixture of HDPE and PP in the range of ≧85% by weight to ≦98% by weight, The amount of polyolefin blend and thermoplastic microspheres is 100% by weight.

[0069] The foam beads are a) a polyolefin blend consisting of HDPE and random PP; b) thermoplastic microspheres encapsulating a blowing agent; may include:

[0070] PP-UMS PP-UMS refers to polypropylene-based ultra melt strength resin having a melt strength of at least 10 cN, preferably at least 20 cN, preferably at least 30 cN, preferably at least 40 cN, preferably at least 50 cN, preferably at least 60 cN, and most preferably at least 65 cN.

[0071] Melt strength is defined as the maximum (drawdown) force (units: cN) that a molten thread can be pulled with before it breaks, e.g. during a Rheotens® measurement. The Rheotens® measurement is carried out at a temperature of 200° C. A capillary tube of length 20 mm and width 2 mm is used. The starting velocity v0 is set to 9.8 mm / s. The acceleration is 6 mm / s. 2 It is.

[0072] The PP-UMS may have a melt flow rate (MFR) in the range of 1.5 to 3.5 g / 10 min, preferably in the range of 2.0 to 3.0 g / 10 min, and even more preferably in the range of 2.2 to 2.8 g / 10 min, as measured by ISO1133-1:2011 at 230° C. and 2.16 kg load.

[0073] DMS measurements are performed using an ARES G2 rheometer at 200° C., at frequencies from 0.01 rad / sec to 100 rad / sec, at a linear viscoelastic strain of 5%, using 0.5 mm thick plates manufactured according to ISO1872-2:2007.

[0074] a) Zero shear viscosity The PP-UMS may have a zero shear viscosity, as determined by DMS (in this case using a Cross model to fit the viscosity data), of ≧7000 Pascal-seconds, more preferably ≧10000 Pascal-seconds, more preferably ≧15000 Pascal-seconds, more preferably ≧20000 Pascal-seconds, and even more preferably ≧23000 Pascal-seconds.

[0075] b) Viscosity ratio (VR) VR is the complex viscosity at a given frequency, η, expressed as the complex viscosity at a frequency of 0.01 rad / sec (η 0.01 ), where complex viscosity is determined by DMS as described above.

[0076] The PP-UMS may have a viscosity ratio, VR100, of ≦0.03, more preferably ≦0.025, where VR100 is the complex viscosity (η 100 ) to the complex viscosity (η 0.01 ) is defined as the ratio

[0077] The PP-UMS may have a viscosity ratio, VR10, of ≦0.08, more preferably ≦0.07, where VR10 is the complex viscosity (η 10 ) to the complex viscosity (η 0.01 ) is defined as the ratio

[0078] The PP-UMS may have a viscosity ratio, VR1, of ≦0.22, more preferably ≦0.20, where VR1 is the complex viscosity (η 1 ) to the complex viscosity (η 0.01 ) is defined as the ratio

[0079] The PP-UMS may have a viscosity ratio, VR0.1, of ≦0.50, more preferably ≦0.46, where VR0.1 is the complex viscosity (η 0.1 ) to the complex viscosity (η 0.01 ) is defined as the ratio

[0080] PP-UMS grades are commercially available, one example is PP-UMS HEX17112 from SABIC.

[0081] Thermoplastic microspheres encapsulating blowing agents. The term thermoplastic microspheres is to be understood as polymeric particles in which a blowing agent is encapsulated.

[0082] Thermoplastic microspheres are known in the art and are described in detail, for example, in EP1981630A1, US3615972, US3945956, EP486080, US5536756, US6235800, US6235394, US6509384, EP1054034, EP1288272, and EP1408097, and WO2004 / 072160. Thermoplastic microspheres are commercially available, for example, from AkzoNobel under the trade name Expancel.

[0083] In such microspheres, the encapsulated blowing agent is typically a liquid with a boiling temperature below the softening temperature of the thermoplastic polymer shell. Upon heating, the blowing agent vaporizes, thereby increasing the internal pressure, causing the microsphere to expand, typically to about 2 to about 5 times its diameter. Foaming occurs when a temperature is reached above the glass transition temperature (Tg) of the polymeric microsphere shell and when the internal pressure is high enough to overcome the elastic modulus of the shell.

[0084] The microspheres may have a spherical shape. The microspheres may be impermeable to the blowing agent. The blowing agent may be present in an amount ranging from 5 to 95 volume percent.

[0085] The diameter of the microspheres may range from ≧0.5 μm to ≦0.5 centimeters before foaming. Preferably, the diameter ranges from ≧0.5 μm to ≦50 μm before foaming. More preferably, the diameter ranges from ≧0.5 to ≦40 μm before foaming. Even more preferably, the diameter ranges from ≧5 to about ≦40 μm before foaming.

[0086] Thermally expandable microspheres can be synthesized by suspension polymerization using radical polymerization. In general, ethylenically unsaturated monomers are polymerized in the presence of a blowing agent. A wide variety of monomers can be used to prepare microspheres, including their homopolymers or copolymers.

[0087] Typical examples are alkenyl aromatic monomers such as styrene, methylstyrene, and ethylstyrene, vinylbenzyl chloride and other vinyl compounds such as vinyl acetate; vinyl propionate; butyl butyrate; vinyl ethers, vinylidene chloride; aryl butyl ethers; aryl glycidyl ethers; unsaturated carboxylic acids such as (meth)acrylic acid or maleic acid; alkyl (meth)acrylamides, and the like, as well as combinations thereof.

[0088] Other examples are acrylate monomers such as methyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, butyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, 2-ethylhexyl acrylate, ethyl methacrylate, iso-butyl acrylate, t-butyl acrylate, n-octyl acrylate, stearyl acrylate, 2-hydroxyethyl acrylate, polyethylene glycol acrylate, methoxypolyethylene glycol acrylate, glycidyl acrylate, dimethylaminoethyl acrylate, diethylaminoethyl acrylate, etc., vinylidene chloride, butadiene.

[0089] Further examples of polymerizable monomers may include unsaturated nitrile monomers, such as acrylonitrile, methacrylonitrile, and the like; (meth)acrylic acid alkyl esters. A crosslinking agent may be added.

[0090] All of the above mentioned monomers may be used individually or in combination of two or more of them.

[0091] The microspheres may contain a wide variety of blowing agents. They may be volatile fluid-forming agents, such as aliphatic hydrocarbons, such as ethane, ethylene, propane, propene, n-butane, isobutane, n-pentane, isopentane, neopentane, n-hexane, heptane, octane, isooctane (2,2,4-trimethylpentane) and petroleum ether; tetraalkylsilanes, such as tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, and trimethyl-n-propylsilane, and mixtures thereof. Among these, preferred are isobutane, petroleum ether, and mixtures thereof. These blowing agents may be used individually or in combination of two or more of them.

[0092] The present invention also relates to the use of such thermoplastic microspheres for producing expandable beads.

[0093] Characteristics of foam beads The expandable beads may have a spherical, rod-like, worm-like, irregular or any other shape. Preferably, the beads have a spherical shape.

[0094] For all shapes, the bead aspect ratio (D 1 / D 2 ) may be in the range of ≧1.0 to ≦1.40, preferably ≧1.0 to ≦1.30, preferably ≧1.0 to ≦1.20, preferably ≧1.0 to ≦1.18.

[0095] D1 and D2 should be understood as the average diameter of the beads. From a representative sample of beads, the smallest and largest diameters of at least 50 beads are measured, and the average values ​​obtained are D1 and D2. 2 is related to the minimum bead diameter for non-spherical particles, and D 1is related to the maximum diameter. The diameter can be measured by known methods, for example those described in ISO 13322-1 (2014) and ISO 13322-2 (2006). The aspect ratio is the ratio of the maximum diameter D of the bead to the maximum diameter D of the bead. 1 The minimum diameter D 2 It needs to be understood as a ratio to.

[0096] Preferably, the expandable beads have a diameter D2 in the range of ≧0.5 to ≦2.5 mm, preferably, the expandable beads have a diameter D2 in the range of ≧0.5 to ≦2.0 mm, preferably in the range of ≧0.8 to ≦2.0 mm, preferably in the range of ≧0.8 to ≦1.8 mm, preferably in the range of ≧0.8 to ≦1.5 mm, preferably in the range of ≧0.8 to ≦1.20 mm.

[0097] The diameter and aspect ratio of the beads are important for foamability and application. Small diameters and aspect ratios result in low foamability, e.g. Steam Chest Molding ensures tight mold packing, resulting in an article with tightly packed beads and efficient bonded bead foam interfaces. Good inter-bead bonding is important to the mechanical properties of the article, since cracks usually form and propagate at the inter-bead bonds.

[0098] The small diameter and aspect ratio of the beads is particularly important for thin walled articles having article cross sectional thicknesses in the range of 5 to 20 mm in order to obtain a smooth surface of the article.

[0099] More particularly, the present invention relates to expandable beads, which include a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The aspect ratio of the bead diameter, defined as the ratio of the maximum diameter D1 to the minimum diameter D2, is in the range of ≧1.0 to ≦1.40, more preferably ≧1.0 to ≦1.20, and the minimum diameter D2 of the bead is in the range of ≧0.5 to ≦2.5 mm.

[0100] Preferably, the expandable beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The aspect ratio of the bead diameter, defined as the ratio of the maximum diameter D1 to the minimum diameter D2, is in the range of ≧1.0 to ≦1.40, and the minimum diameter D2 of the bead is in the range of ≧0.5 to ≦2.0 mm, preferably in the range of ≧0.8 to ≦2.0 mm, preferably in the range of ≧0.8 to ≦1.8 mm, preferably in the range of ≧0.8 to ≦1.5 mm, preferably in the range of ≧0.8 to ≦1.20 mm.

[0101] Preferably, the expandable beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The aspect ratio of the bead diameter, defined as the ratio of the maximum diameter D1 to the minimum diameter D2, is in the range of ≧1.0 to ≦1.20 mm, and the minimum diameter D2 of the bead is in the range of ≧0.5 to ≦2.0 mm, preferably in the range of ≧0.8 to ≦2.0 mm, preferably in the range of ≧0.8 to ≦1.8 mm, preferably in the range of ≧0.8 to ≦1.5 mm, preferably in the range of ≧0.8 to ≦1.20 mm.

[0102] Preferably, the expandable beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The aspect ratio of the diameter of the beads, defined as the ratio of the maximum diameter D1 to the minimum diameter D2, is in the range of ≧1.0 to ≦1.40, the minimum diameter D2 of the beads is in the range of ≧0.5 to ≦2.5 mm, and the expandable beads are ≧70% to ≦98% by weight, Preferably >75% by weight to ≦98% by weight, More preferably ≧80% by weight to ≦98% by weight, More preferably, it comprises polyolefin in the range of ≧85 wt.% to ≦98 wt.%; The total amount of polyolefin and thermoplastic microspheres is 100% by weight.

[0103] More preferably, the expandable beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The aspect ratio of the diameter of the beads, defined as the ratio of the maximum diameter D1 to the minimum diameter D2, is in the range of ≧1.0 to ≦1.20, the minimum diameter D2 of the beads is in the range of ≧0.5 to ≦2.5 mm, and the expandable beads are ≧70% to ≦98% by weight, Preferably >75% by weight to ≦98% by weight, More preferably ≧80% by weight to ≦98% by weight, More preferably, it comprises polyolefin in the range of ≧85 wt.% to ≦98 wt.%; The total amount of polyolefin and thermoplastic microspheres is 100% by weight.

[0104] The standard deviation (StD) of the bead diameters D1 and / or D2 may also be as small as possible, since this ensures a homogeneous and dense filling of the mould and a smooth surface of the article. Preferably, the standard deviation of the diameters D1 and / or D2 is in the range of 0.08 to 0.50 mm, more preferably 0.1 to 0.40 mm, even more preferably 0.1 to 0.30 mm, even more preferably 0.1-0.25 mm.

[0105] Furthermore, the expandable beads have a strength of ≧430 to ≦600 kg / m 3 in the range of ≧440 to ≦600 kg / m 3 in the range of ≧440 to ≦560 kg / m 3 The bulk density may be in the range of 0.01 to 0.05, as measured by ISO 60 (1977).

[0106] An advantage of the beads according to the invention is their storage stability, which means that if the same conditions are used to expand the beads, after a certain storage period the beads can be expanded to achieve the same bulk density as compared to the expansion process immediately after the preparation of the beads.

[0107] Thus, the beads are stable and do not lose their expandability over a certain period of time. As a result, for example, there is no need to store them under pressure in a container. Thus, the resulting expandable beads can be stored or transported as prepared. For example, pre-expanding the beads with steam after storage at atmospheric pressure can result in foamed beads with sufficient expansion and low density.

[0108] The beads may have a storage stability of at least 6 months, preferably at least 1.0 year, more preferably at least 1.5 years, more preferably at least 2.0 years.

[0109] The expandable beads have a diameter in the range of ≧0.5 to ≦2.5 mm, preferably in the range of ≧0.8 to ≦2.0 mm, and a compressibility of ≧430 to ≦600 kg / m3 in the range of ≧440 to ≦600 kg / m 3 in the range of ≧440 to ≦560 kg / m 3 and a storage stability of at least 6 months, preferably at least 1.0 year, more preferably at least 1.5 years, and more preferably at least 2.0 years.

[0110] Preferably, the expandable beads have a diameter in the range of ≧0.5 to ≦2.5 mm and a compressibility of ≧430 to ≦600 kg / m 3 and a storage stability of at least six months.

[0111] The beads become expanded when they are heated to a high enough temperature to permit plastic flow and vaporize or volatilize at least a portion of the blowing agent. When the beads are cooled, the polyolefin no longer flows and expands, and retains its increased dimensions. This volume increase is retained upon cooling, increasing the density to approximately 600 kg / m 3 to about 20 kg / m 3 This unique expandability allows for a very large reduction in the density of the beads, making them excellent for many applications.

[0112] The expandable beads have a compressibility of ≧20 to ≦350 kg / m after expansion. 3 in the range of ≧20 to ≦200 kg / m 3 in the range of ≧20 to ≦150 kg / m 3 in the range of ≧20 to ≦100 kg / m 3 The bulk density may be in the range of 0.01 to 0.05, as measured by ISO 60 (1977).

[0113] The expansion ratio ER of a bead is defined as the ratio of its bulk density before expansion to its bulk density after expansion (ER=bulk density before expansion / bulk density after expansion).

[0114] The expansion ratio ER of the beads is in the range of ≧1.4 to ≦45, preferably ≧2.0 to ≦45, preferably ≧3.0 to ≦45, preferably ≧5.0 to ≦45, preferably ≧5.0 to ≦15, more preferably ≧5.0 to ≦12.

[0115] Preferably, the expandable beads have a diameter in the range of ≧0.5 to ≦2.5 mm and a compressibility of ≧430 to ≦600 kg / m 3 , storage stability of at least 6 months, and after foaming thereof, a bulk density in the range of ≧20 to ≦350 kg / m 3 in the range of ≧20 to ≦200 kg / m 3 in the range of ≧20 to ≦150 kg / m 3 in the range of ≧20 to ≦100 kg / m 3 The bulk density is in the range of

[0116] Process for producing expandable beads The present invention also relates to a process for making the expandable beads.

[0117] One or more polyolefins can be fed into the extruder through one or more input openings, where they are melted and mixed. One or more polyolefins can be fed into the extruder as a blend, a dry blend, or as a single component through different input openings. Thermoplastic microspheres can be fed into the extruder through an input opening at a point downstream from the input opening of the extruder and before the exit opening. The input opening for adding thermoplastic microspheres is preferably located about 2 / 3 of the way from the input opening to the exit opening. The input opening can feed the microspheres into the melt to form a mixture of one or more polyolefins and thermoplastic microspheres.

[0118] The process of mixing the components is not particularly limited. Any mixing or kneading device may be used. Preferably, the components are mixed in a single screw extruder, a twin screw extruder, or a multi-screw extruder.

[0119] During the mixing step, one or more additives and / or one or more nucleating agents may be added. Preferably, the one or more additives and / or one or more nucleating agents are added after the one or more polyolefins are fed into the extruder through one or more input openings. The one or more additives and / or one or more nucleating agents may be fed through one or more input openings and dosed into the polyolefin mixture. Preferably, the additives are fed into the extruder before the microspheres are fed into the extruder. The one or more additives and / or one or more nucleating agents may include those described below. Each of these may be utilized in greater or lesser amounts depending on the desired and required final properties of the foamed product.

[0120] After mixing, the molten mixture can be extruded through an underwater pelletizing die into contact with moving water or any other suitable fluid, which cools the melt and inhibits foaming of the mixture. A preferred fluid is water. The water may be optionally pressurized. Other suitable fluids can include fluids that are non-reactive and immiscible with one or more polyolefins, such as nitrogen, helium, alcohols, polyols, or glycols. As the mixture exits the die and is cooled by a liquid, preferably water, the mixture can be cut into beads by rotating a cutting blade in a cutting chamber that contacts the face of the die. The moving water can carry the pellets to a drying area, where the beads can be removed from the water and dried.

[0121] The die opening through which the mixture passes defines the overall shape of the resulting beads. The die opening may be any shape to produce beads, including rectangular, square, circular, oval, or even asymmetrical shapes. The die may have multiple openings so that the expandable beads exit the die as beads.

[0122] A typical apparatus is shown in FIG.

[0123] According to the present invention, the process for producing expandable beads comprises the steps of: (a) feeding one or more polyolefins into a melt mixing device, the polyolefin being selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; (b) heating the one or more polyolefins to melt; (c) introducing the microspheres into the melt mixing device to form a mixture with one or more polyolefins in the melt mixing device; (d) feeding the mixture into a heated die containing a plurality of holes on a surface thereof grouped into pods; (e) extruding the mixture through the holes into an underwater pelletizer, which may optionally utilize a pressurized fluid system; (f) cutting the mixture to form beads; (g) removing the beads from the water; (h) drying the beads; Includes. [Brief description of the drawings]

[0124] [Figure 1] Schematic diagram of a one-step extrusion apparatus for the process of producing expandable beads, comprising: 1 - polymer inlet 2 - inlet for thermoplastic microspheres containing blowing agent 3 - extruder 4 - melt pump 5 - polymer diverter 6 - die plate 7 - cutting chamber 8 - cutter motor 9 - water bath 10 - water pump 11 - pellet dryer 12 - collection vessel DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0125] Additives The polymer and resin composition in the resin composition according to the present invention may contain additives such as nucleating and clarifying agents, stabilizers, mold release agents, fillers, plasticizers, antioxidants, lubricants, antistatic agents, scratch resistance agents, thermal conductivity modifiers, high performance fillers, pigments and / or colorants, impact modifiers, foaming agents, acid scavengers, regenerating additives, coupling agents, antibacterial agents, anti-fog additives, lubricants, anti-blocking additives, flame retardants, clays, and polymer processing aids.These additives are well known in the art.Those skilled in the art will select the type and amount of additives so that they do not adversely affect the desired properties of the composition.

[0126] Nucleating Agent Nucleating agents provide numerous nucleation sites, each of which can induce the formation of cells during foaming. Nucleating agents control the cell morphology (i.e., cell number, cell size, and their distribution) in thermoplastic foams.

[0127] Examples of nucleating agents are talc, magnesium silicate, carbon black, graphite, titanium dioxide, calcium carbonate, calcium hydroxide, calcium stearate, zinc stearate, aluminum stearate, azodicarbonamide, and sodium bicarbonate. Polymeric materials such as nylon and PPO may also be used as nucleating agents. All nucleating agents have a particle size of approximately 1 micrometer or less.

[0128] Preferably, the expandable beads include a nucleating agent. A preferred nucleating agent is calcium carbonate.

[0129] Expandable Beads Expansion and Forming Process The expandable beads can be converted into the desired article in a two-step process: pre-expansion and molding. Each bead comprises a foamable polymer composition that includes a thermoplastic polymer substrate and, dispersed in the substrate, thermoplastic microspheres that encapsulate a blowing agent.

[0130] The bead pre-expansion process can be used to pre-expand the polymeric beads of the present invention. The pre-expansion process can be summarized as converting the shape of the beads into cellular structured spheres with larger volume and smaller density with the aid of a blowing agent.

[0131] Such pre-expansion processes include, for example, steam pre-expansion, infrared oven and hot air oven expansion.

[0132] Very common is the steam pre-expansion process, which can be a batch or continuous process. Steam pre-expansion processes are well known in the art. A person skilled in the art will select the process and process conditions based on the downstream molding operation and the intended use of the foamed beads. It is essential to agitate the expanding beads during pre-expansion to eliminate bead agglomeration. Therefore, the pre-expansion vessel is usually equipped with a centrally located rotating agitator and a stationary breaker bar mounted inside the vessel. In addition, high pressure steam is required to reach a temperature at which the beads soften, i.e. to raise the temperature near the melting point of the polymer. The wet pre-expanded beads are discharged into a fluidized bed, where they are dried by hot air and then transferred to a silo for molding operations.

[0133] Steam Chest A molding process is generally used to shape the pre-expanded beads into the desired article. For expandable polystyrene (EPS) and expanded PP beads Steam Chest Molding processes are also well known in the art.

[0134] Briefly, the beads are processed into an article by fusing them together using steam. The particles are fed into a mold, compressed, and then perfused with steam, which heats the surface portions of the beads and causes them to fuse together. The fused article is cooled in the mold and then removed therefrom.

[0135] Unlike EPS, existing commercially available expanded PP beads do not contain any blowing agent and must be compensated for by mechanical means during the molding process. The expandable beads of the present invention can overcome this problem because they contain residual blowing agent to assist in sintering the beads by further expanding in the mold. The beads are also suitable for molding by other fusion processes, for example without steam.

[0136] Articles of desired shape can be made by filling a closed cavity with pre-expanded beads under pressure and heating to a temperature above their softening point. This results in further expansion of the beads to fill the free volume and fuse the beads along the bond interfaces. After a cooling period (reduction of pressure), the molded part is dimensionally stable and can be removed from the mold.

[0137] Goods Furthermore, the present invention relates to foam beads or articles, preferably molded articles, preferably i) automotive parts, preferably bumpers, steering column pads, sunshades, arm rests, head rests, seats, wheel well liners, side impact protectors, and battery covers, and / or ii) Packaging materials, preferably dunnage trays, shipping containers, medical and food containers, which require temperature control, sterility and damage protection during thermal and sound management of transport; and / or iii) Equipment, safety and recreational items The present invention relates to the use of such expandable beads for producing moldings for a pharmaceutical composition.

[0138] The present invention also provides Steam Chest It can also relate to the use of such expandable beads for the manufacture of articles by molding. Preferably, the beads are sintered by further expanding in a mold. Preferably, the beads do not need to be compensated during the molding process.

[0139] Furthermore, the present invention relates to a method for producing an article, preferably a molded article, by molding the expandable beads, preferably a molded article produced by fusing the beads, more preferably Steam Chest It relates to a process for making molded articles, more preferably automotive parts and / or fittings and / or safety and recreational items.

[0140] Furthermore, the present invention relates to a method for producing an article, preferably a molded article, by molding the expandable beads, preferably a molded article produced by fusing the beads, more preferably Steam Chest In a process for making molded articles, more preferably automotive parts and / or furniture and / or safety and recreational items, the expandable beads are a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Includes.

[0141] Preferably, the process produces bumpers, steering column pads, sunshades, arm rests, head rests, seats, wheel well liners, side impact protectors, and battery covers, and / or packaging materials, preferably dunnage trays, shipping containers, medical and food containers, which require temperature control, sterility and damage protection during thermal and sound management of transportation.

[0142] Furthermore, the present invention relates to, for example, Steam Chest For the process of making articles by molding, pre-expanded beads are packed under pressure into a preferably enclosed cavity and heated above their softening point, thereby fusing the beads along their bonding interfaces to produce an article of the desired shape.

[0143] Furthermore, the present invention relates to an article, preferably a molded article, comprising expandable beads according to the invention or obtainable by the process according to the invention, more preferably a molded article made by fusion of the beads, more preferably Steam Chest Concerning molded articles.

[0144] The present invention also relates to an article, preferably a moulded article, made from the expandable beads according to the invention or made from the expandable beads obtained or obtainable by the process according to the invention, preferably a moulded article. Steam Chest Concerning molded articles.

[0145] The present invention also relates to an article made from expandable beads, preferably a molded article, preferably a molded article made by fusing beads, preferably Steam Chest Regarding molded products, the expandable beads are: a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Includes.

[0146] Preferably, the articles are parts for automotive applications, such as bumpers, steering column pads, sunshades, arm rests, head rests, seats, wheelhouse liners, side impact protectors, and battery covers, made from the expandable beads according to the invention or made from the expandable beads obtained or obtainable by the process according to the invention, and / or packaging, such as dunnage trays, shipping containers, medical and food containers, that require temperature control, sterility and damage protection during thermal and sound management of transportation.

[0147] The foamed beads and foamed articles made from the expandable polymer beads of the present invention have a foaming capacity of 10 to 400 kilograms per cubic meter (kg / m 3 ), preferably 100 kg / m 3More preferably, 50 kg / m or less 3 It may have a density within the following ranges:

[0148] Typically, foamed beads and foamed articles made from the expandable polymer beads of the present invention are rated to a strength of 10 kg / m to ensure mechanical integrity during handling. 3 More than 20kg / m 3 More than 30kg / m 3 More preferably, the density is between 30 and 50 kg / m 3 A lower density for foam beads and foam articles is desirable to reduce manufacturing and shipping costs as well as for ease of handling. Foam density is determined by the method of ISO 845-95.

[0149] The open cell content of foamed beads and foamed articles made from the expandable beads of the present invention can be 30% or less, preferably 10% or less, more preferably 5% or less, even more preferably 2% or less. The open cell content can be 1% or less, or even 0%. The open cell content is determined by the method of ASTM D6226-05.

[0150] The invention will now be illustrated by the following non-limiting examples.

[0151] Working Example material The materials listed in Table 1 were used. [Table 1]

[0152] Measurement method Bead diameters are measured directly from micrographs according to ISO13322-1 (2014). Beads are attached to standard slides and viewed with an Olympus 510 digital optical microscope. Images of at least 50 beads are recorded in reflected light mode. Both bead diameters D1 and D2 are measured using the image analysis software Image J.

[0153] The bulk density of the raw beads is measured by using a 1 or 2 liter cylinder and collecting the beads into the cylinder to its full capacity, aligning the surface horizontally against the cylinder and weighing the beads.

[0154] The bulk density of the foamed beads is also measured by using a 1 or 2 liter cylinder and collecting the foamed beads into the cylinder to its full capacity, aligning its surface horizontally against the cylinder and weighing the foamed beads (these beads should be free of agglomerates or lumps).

[0155] Preparation of beads The expandable beads were prepared using a twin screw extruder manufactured by Berstorff and an underwater pelletizing system manufactured by Nordson BKG, using the conditions in Table 2. [Table 2]

[0156] Bead foaming The foaming data reported in the table below was generated using a hot air oven. The oven was preheated to 180° C. and a known amount of beads was placed in an open aluminum pan and placed in the oven. After the designated time, the sample was removed from the oven and the bulk density of the beads was measured using a quantitative container. [Table 3a] [Table 3b] [Table 4] [Table 5] [Table 6a] [Table 6b]

[0157] The shelf life of the beads was demonstrated by pre-expanding (or molding) the beads after storing the product at room temperature for various time intervals. The pre-expanding (or molding) experiments were carried out under identical conditions to the experiments using fresh beads. The results are shown in Table 7. [Table 7]

[0158] The results presented above clearly demonstrate the feasibility of the process to make expandable beads using a composition of PP and microspheres, or a composition of PP blends with other polyolefins and microspheres.

[0159] The results in Table 7 show that the beads are storage stable. Storage stable in this context means that the beads can be stored for a certain period of time without losing their properties. In particular, this means that the beads can be foamed and expanded with the same results as when the beads are expanded immediately after production, as long as the same process conditions are used.

[0160] It was possible to achieve the same low bulk density by expansion both immediately after the preparation of the beads and after storing the unexpanded beads for at least six months. This means that the beads can be stored and transported in the unexpanded state before expanding them, which is a huge advantage and saves on transportation costs.

Claims

1. 1. Expandable beads, comprising: a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; Including, The aspect ratio of the diameter of the bead, defined as the ratio of the maximum diameter D1 to the minimum diameter D2, is in the range of ≧1.0 to ≦1.40, and the minimum diameter D2 of the bead is in the range of ≧0.5 to ≦2.5 mm. Expandable beads.

2. the expandable beads comprise from ≧70% by weight to ≦98% by weight of the polyolefin; The total amount of the polyolefin and the thermoplastic microspheres is 100% by weight.

2. The expandable beads of claim 1.

3. The polypropylene has a melt flow index (MFI) in the range of ≧5 to ≦60 g / 10 min, measured according to ISO 1133 at 230° C. and a load of 2.16 kg; 3. Expandable beads according to claim 1 or 2.

4. Expandable beads according to any one of claims 1 to 3, wherein the polypropylene is selected from homopolymer PP and random PP copolymers.

5. the polyethylene is a linear low density polyethylene (LLDPE) and / or a high density polyethylene (HDPE), the linear low density polyethylene (LLDPE) having an MFI in the range of ≧5 to ≦70 g / 10 min, measured according to ISO 1133 at 190° C. and 2.16 kg; and / or ≧910 to ≦940 kg / m when measured according to ISO 1183 3 having a density in the range of the high density polyethylene (HDPE) has an MFI in the range of ≧5 to ≦70 g / 10 min, measured according to ISO 1133 at 190° C. and 2.16 kg load; and / or ≧940 to ≦970 kg / m when measured according to ISO 1183 3 having a density in the range The expandable beads according to any one of claims 1 to 4.

6. and / or has a diameter D2 in the range of ≧0.8 to ≦2.0 mm; ≧430 to ≦600 kg / m 3 and / or Have a shelf life of at least six months; The expandable beads according to any one of claims 1 to 5.

7. After the expansion of the expandable beads, ≧20 to ≦350 kg / m 3 having a bulk density in the range of The expandable beads according to any one of claims 1 to 6.

8. The thermoplastic microspheres have a size in the range of ≧0.5 μm to ≦50 μm. The expandable beads according to any one of claims 1 to 7.

9. 9. The expandable beads according to any one of claims 1 to 8, wherein the beads comprise a nucleating agent, the nucleating agent being calcium carbonate.

10. (a) feeding one or more polyolefins into a melt mixing device, said polyolefins being selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; (b) heating the one or more polyolefins to melt; (c) introducing microspheres into said melt mixing device to form a mixture with said one or more polyolefins in said melt mixing device; (d) feeding the mixture into a heated die containing a plurality of holes on its surface grouped into pods; (e) extruding the mixture through the holes into an underwater pelletizer, which may optionally utilize a pressurized fluid system; (f) cutting the mixture to form beads; (g) removing the beads from the water; (h) drying the beads; A process for producing the expandable beads according to any one of claims 1 to 9, comprising:

11. Use of the expandable beads according to any one of claims 1 to 9 for the production of a steam chest moulding.

12. Use of the expandable beads according to any one of claims 1 to 9, i) automotive parts; and / or ii) packaging materials; and / or iii) Equipment, safety and recreational items 23. Use of expandable beads for producing a steam chest molding for.

13. A process for making an article by shaping the expandable beads according to any one of claims 1 to 9 or obtained or obtainable by the process according to claim 10.

14. An article made from expandable beads according to claims 1 to 9 or obtained or obtainable by the process according to claim 10.

15. 1. A process for making a steam chest molded article by molding expandable beads, the expandable beads comprising: a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; The process includes:

16. A steam chest molding made from expandable beads, the expandable beads comprising: a) a polyolefin selected from polyethylene (PE), polypropylene (PP), and mixtures thereof; b) thermoplastic microspheres encapsulating a blowing agent; A steam chest molding made from expandable beads, comprising:

Citation Information

Patent Citations

  • Thermally expandable microcapsule and foam-molded article

    EP2360221B1

  • Preparation of foamable polyethylene resin

    JP1987280237A

  • Pulp bead and pulp formed part using this

    JP2000086801A

  • Phenolic syntactic foam composition

    JP2006517238A

  • Thermally expandable microcapsule and foam-molded article

    JP2010132860A